Occupational Exposure to Blood and Body Fluids Among Health Care Professionals in Bahir Dar Town, Northwest Ethiopia - Muluken Azage Yenesew; Gedefaw Abeje Fekadu (Elsevier, 2014)
Background: Health care professionals (HCPs) are at high risk of contracting blood-borne infections due to their occupational exposure to blood and body fluids (BBFs). The incidence of these infections among HCPs are higher in low income countries such as Ethiopia. The aim of the study was to investigate the extent of occupational exposure to BBFs and its associated factors among HCPs in Bahir Dar town, Ethiopia. Methods: A cross-sectional study was used from October 1, 2012 to October 30, 2012. Three hundred and seventeen HCPs were included in the study using a simple random sampling technique. The data were collected using a structured questionnaire and analyzed using SPSS version 16. Bivariate and multivariate analyses were used to identify the factors related to exposure to BBFs. Results: Two hundred and nine (65.9%) HCPs were exposed to BBFs in the past year, of which 29.0% were needlestick injuries. Work experience [adjusted odds ratio (AOR) 4.13, 95% confidence interval (CI) 1.56-10.91], inconsistent use of gloves (AOR 1.98, 95% CI 1.04-3.43), and not complying with standard precautions (AOR 1.80, 95% CI 1.00-3.22) were the factors associated with occupational exposure to BBFs. Conclusion: A high proportion of HCPs was exposed to BBFs in this study. Occupational exposure to BBFs was determined by the use of gloves and not complying with standard precautions. Ensuring the availability of gloves, training about standard precautions, and motivation of HCPs to implement standard precautions should be emphasized to avoid such exposures.